Financial Management in Practice - Onochie, Joe Chukwuemeka (Enugu Emeka Adichie Publisher, 1979)
Financial Management in Practice aims, as the title suggests, to go beyond a classic academic approach to financial management, by illustrating theoretical insights with concrete cases. The book is structured according to this ethos of practicality. Beginning with a description of the current banking and entrepreneurial landscape, the book proceeds to examine the basic concept of financial management. The business plan and financial plan then become the working tools in the author's search for optimal financing and in determining the value of the enterprise. This is followed by an analysis of all forms of debt financing. Subsequently the book examines mezzanine financing and formal and informal venture capital, including business angels and crowdfunding. This form of financing requires another reading of the business plan. The central focus is no longer on the repayment capacity, but on the potential added value to the investment. Of course, this also applies to initial public offerings, which are discussed later on. The book concludes with a review of the Basel Accords, from the point of view of the entrepreneur. With this, the author provides ammunition for managers confronted with banks or venture capitalists who claim that some actions are not possible because of Basel.
Includes index.
Keywords: Accountancy in Nigeria; Business enterprises; Financial Management; Finance